Spiked Zinger Lily (hedychium Spicatum) : Identification of Superior Genotypes from Indian Himalayan Region - Negi, K. S.; Koranga, S. S.; Ojha, S. N.; Pandey, M. M.; Rawat, A. K. S.; Raina, A. P.; Rayal, A. (Indian Forester, 2014)
Spiked Zinger Lily, a perennial rhizomatous herb, belongs to family Zingiberaceae, commonly known as ’Kapur-kachari’ widely available in moist, damp-shady evergreen forests and popular in traditional systems with several ethnobotanical notes. For identification of superior genotypes, a total of 34 accessions were collected from Indian Himalayan Region along with passport information. Rhizomes of all accessions were chopped, dried and subjected to Clevenger Hydro-distillation unit for essential oil extraction and observed 0.06-6.12% oil yield. In addition to this 1, 8 cineole (8.22 -58.15 %) was observed as a major constituent of the essential oils on Gas Chromatography (GC). Essential oil content and major chemical constituent 1, 8 cineole, both the parameters revealed an increasing trend along an altitudinal gradient of 1400-2875 m amsl.